EVALUASI PENGEMBANGAN KOLEKSI SEBAGAI DASAR MEMAHAMI PROBLEMATIKA DALAM PERPUSTAKAAN (STUDI KASUS DINAS KEARSIPAN DAN PERPUSTAKAAN PROVINSI GORONTALO) - Ade Yul Pascasari Katili (Jurnal Pustaka Ilmiah, 2017)
This paper aims to understand how the collection development activities, and evaluation activities in Department of Achives and Library of Gorontalo Province. The methodology used is a conceptual theoretical approach using studies from various printed sources and scientific journals and using interviews to supplement the data. Collection development is basically an activity related to the development of library collections including selection, selection policy determination, assessment of the needs of users and potential users, collection analysis, collection user reviews, budgetarrangements, collection evaluations, identification of collections required by users, until the plan to cooperate. After analyzing the theories that have been explained with the reality in the Department of Achives and Library of Gorontalo Province, the library has conducted evaluation activities in accordance with the existing flow by determining when the evaluation activities will be implemented, determine the objectives, start theevaluation activities by selecting the techniques used in evaluating the collection. It is expected that the library can continue to implement evaluation activities correctly so that problems related to require the information can be overcome well.